ANALISIS IMPLEMENTASI STRATEGI PERKULIAHAN KOLABORATIF BERBASIS MASALAH DALAM MENGEMBANGKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS,KEMAMPUAN KOMUNIKASI MATEMATIS, ANALISIS IMPLEMENTASI STRATEGI PERKULIAHAN KOLABORATIF BERBASIS MASALAH DALAM MENGEMBANGKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS, KEMAMPUAN KOMUNIKASI MATEMATIS,DAN KEYAKINAN TERHADAP PEMBELAJARAN MATEMATIKA - Widjajanti, Djamilah Bondan (2010)
Most of students consider mathematics as a difficult lesson. This assumption is partly based on the experience they gained during their learning of mathematics. Therefore, mathematics teachers play an important role in building the students' belief towards mathematics lesson. In order to be able to give a fair picture of mathematics to students, mathematics prospective teachers need to have mathematical problem-solving ability, mathematical communication skill, as well as positive belief towards learning mathematics. Unfortunately, they are weak in those skills. A collaborative problem-based course strategy is offered as an alternative to overcome such problems concerning the weakness of mathematics prospective teachers. This research is conducted within that background. This study aimed to analyze the implementation of collaborative problem-based course strategy in developing mathematical problem solving ability, mathematical communication skill, and belief in learning mathematics, for mathematics prospective teachers of both regular and non-regular programs. Mathematics prospective teachers from regular program are the students who were accepted via talented-student selection program (Penelusuran Bibit Unggul/PBU) or general selection system (SNMPTN). Mathematics prospective teachers from non-regular program are the students who were accepted via admission systems other than PBU and SNMPTN. This study is an experimental research. The design of this study is 2 × 2 factorial with three dependent variables. Subjects are 83 students of Mathematics Education Study Program, Faculty of Mathematics and Natural Sciences, Yogyakarta State University, who took the Discrete Mathematics course in September-December 2009 semester. The instruments used were a test on problem-solving ability, a test on mathematical communication skill, a psychological scale to measure the increase of students' belief, observation sheets, and interview guides. The data analysis technique made use of two-way MANOVA with the significance level α = 0.05. It can be concluded that the collaborative problem-based course strategy is more superior to the conventional course strategy in terms of developing mathematical problem solving ability, mathematical communication skill, and students' belief towards learning mathematics, both for students of regular and non-regular programs. The other advantages are the readiness, liveliness, and enthusiasms of those mathematics prospective teachers who follow the course with collaborative problem-based strategy are higher compared to those who took the course with conventional strategy.